Poliomyelitis-like illness after acute asthma. Issue 9 (September 1977) - Ilett, S J; Pugh, R J; Smithells, R W
Abstract : Two children had pain in one arm, followed by weakness and wasting, after an acute exacerbation of bronchial asthma. Similar cases in which a poliomyelitis-like illness was associated with acute asthma have been reported, but the relationship between the two remains conjectural.